Structural and functional features of healing of tiba fractures using apiphonophoresis - Gozhenko, A.; Pavlenko, K.; Chivga, V. (Journal of Education, Health and Sport, 2024)
Modernity is defined as an "epidemic of trauma". Every year, up to 2 million adults and 300 thousand children, residents of Ukraine, receive various injuries. Since injuries and their consequences are the cause of disability in 89% of the working population, the problem of trauma, including bone fractures, becomes not only a medical but also a social problem. In this regard, the treatment of injuries in general and fractures in particular remains very relevant. The aim of the work was to compare the results of restorative treatment of fractures of tubular bones using apiphonophoresis with a variable dose of bee venom and apiphonophoresis with a fixed dose of "Apizarthron". The materials of this study were the data obtained in the study of 60 white male rats of the Wistar line of outbred breeding, weighing 180-200 g. Our studies have established that apiphonophoresis, performed in a course, accelerates the process of restoring bone integrity in fractures. This is due to the increase in the activity of osteocytes, periosteocytes, and the protein-synthesizing functions of these cells.